Geographical inequalities in breast cancer incidence, mortality and late stage at diagnosis in Cyprus. (30th September 2020) - Demetriou, C A; Quattrocchi, A; Heraclides, A; Constantinou, C; Marcou, Y; Demetriou, A; Scoutellas, V; Kolokotroni, O
Abstract: Background: A national breast cancer (BC) screening programme, targeting women 50-69 years old, was introduced in Cyprus in 2007. This study aims to assess rural/urban differences in BC incidence, tumour stage at diagnosis (TSD) and mortality, since 2004 and since the introduction of the screening programme. Methods: Data were obtained for 6589 new cases of BC (diagnosis 2004-2016) from a national population-based cancer registry (1998-today) in Cyprus. TSD was recorded according to the Surveillance, Epidemiology, and End Results categories. We defined late TSD as regional or distant stage. Unknown stages were excluded. We linked cases to the population census data and place of residence (rural/urban) and calculated incidence and mortality rate ratios (RR) by place of residence. We conducted logistic regression to measure the association between place of residence and TSD or mortality, adjusting for sex, age, ethnicity, smoking and marital status. Adjusted odds ratios (aOR) and 95% confidence intervals (CI) are reported. Results: Since 2004, 54.7% of BC cases were diagnosed at localised stage, 40.6% at regional stage and 4.7% at distant stage. Incidence, but not mortality, rate for all BC was higher in urban than in rural areas (RRincidece=1.22;95%CI=1.51-1.28 and RRmortality=1.10;95%CI=0.97-1.24). Rural place of residence was associated with higher odds of late TSD (aOR=1.34; 95%CI=1.15-1.58) and death (aOR=1.36; 95%CI=1.11-1.68). After the introduction of the screening programme, for the targeted age group, rural place of residence was still associated with higher odds of late TSD (aOR=1.31; 95%C= 1.03-1.67), but not with death (p > 0.05). Conclusions: Even though BC incidence is higher in urban than in rural areas, women residing in rural areas had higher odds of late TSD and death. The introduction of the national BC screening programme only slightly reduced geographical inequalities in TSD. Further studies are needed to understand and reduce the role of inequalities in TSD. Key messages: Rural/Urban inequalities in TSD are evident among BC cases in Cyprus, diagnosed between 2004 and 2016. The introduction of the national BC screening programme reduced but did not overcome geographical inequalities in TSD.